2022
DOI: 10.1021/acsami.2c16414
|View full text |Cite
|
Sign up to set email alerts
|

Promising Thermally Stable Energetic Materials with the Combination of Pyrazole–1,3,4-Oxadiazole and Pyrazole–1,2,4-Triazole Backbones: Facile Synthesis and Energetic Performance

Abstract: Thermally stable energetic materials have broad applications in the deep mining, oil and natural exploration, and aerospace industries. The quest for thermally stable (heat-resistant) energetic materials with high energy output and low sensitivity has fascinated many researchers worldwide. In this study, two different series of thermally stable energetic materials and salts based on pyrazole–oxadiazole and pyrazole–triazole (3–23) with different explosophoric groups have been synthesized in a simple and straig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…The onset decomposition temperature of all the cocrystals is >222 °C, which is far better than that of NBA (∼173 °C) and the benchmark explosive RDX (210 °C). Among them, NBA:DAG melts (onset: 185 °C; peak: 196 °C) before decomposition and shows excellent thermal stabilities (310 °C), which is better than the heat-resistant explosive HMX (279 °C) and close to HNS (318 °C) . Additionally, the thermal stabilities of NBA/AmTz and NBA/DAG were determined at various heating rates 5, 10, 15, and 20 °C (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The onset decomposition temperature of all the cocrystals is >222 °C, which is far better than that of NBA (∼173 °C) and the benchmark explosive RDX (210 °C). Among them, NBA:DAG melts (onset: 185 °C; peak: 196 °C) before decomposition and shows excellent thermal stabilities (310 °C), which is better than the heat-resistant explosive HMX (279 °C) and close to HNS (318 °C) . Additionally, the thermal stabilities of NBA/AmTz and NBA/DAG were determined at various heating rates 5, 10, 15, and 20 °C (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“… a Onset decomposition temperature (DSC, 5 °C/min). b Crystal density. c Computed HOF. d Detonation pressure. e Detonation velocity. f Impact sensitivity. g Friction sensitivity. h Ref . i Ref . …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Fused heterocycles constitute a large variety of structural scaffolds and recent accomplishments of several research groups globally confirmed that the presence of fused backbones in energetic materials usually enhances the energy and nitrogen content, detonation performance, insensitivity and thermal stability, which enhances their practical applicability. [4][5][6][7][8] Nitrogen-rich fused heterocycles have more extensive N-C, N-N and NvN high-energy bonds in the structure than single-ring heterocycles, which provide high energy content to these compounds. A few combinations of strained fused catenated heterocyclic compounds have also been synthesized and their energetic properties were examined, which showed good thermal stability and insensitivity towards external stimuli such as impact and friction.…”
Section: Introductionmentioning
confidence: 99%